One year prognosis of young Middle Eastern patients undergoing percutaneous coronary interventions - Alhaddad, Zayd I.; Hammoudeh, Rawan A.; Tabbalat, Rinad R.; Khader, Yousef; Alhaddad, Imad A.; Hammoudeh, Ayman J. (International Journal of Research in Medical Sciences, 2016)
Background: There is scarcity of data about the outcome in young Middle Eastern patients who undergo percutaneous coronary intervention (PCI). We sought to assess clinical and coronary angiographic features and one year outcome of young compared with older patients following PCI. Methods: Baseline clinical and coronary angiographic features and major cardiovascular events from hospital admission to one year were assessed in young patients (<45 years of age) compared with older patients (>45 years of age). Results: Of 2426 patients; 308 (12.7%) were young. Young and older patients were predominantly males (76.3% vs. 79.8%; p=0.18) and had similar prevalence of hypertension, diabetes, dyslipidemia, and cigarette smoking. There were no differences between young and older patients in the rates of acute coronary syndrome as an indication for PCI (75.6% vs. 76.1%; p=0.90). The two groups had similar prevalence of one-vessel coronary artery disease (55.2% vs. 58.1%; p=0.37) and intervention for one vessel (74.0% vs. 72.1%; p=0.53). No significant differences were observed in the incidence of in-hospital adverse events in young compared with older patients. Incidence of adverse events in young patients at one year were not different from those in older patients, including cardiac death (3.63% vs. 2.11%), stent thrombosis (3.63% vs. 2.08%), major bleeding (1.30% vs. 1.18%), and coronary revascularization (3.65% vs. 3.24%); all p=NS. Conclusions: Among Middle Eastern patients undergoing coronary intervention; 13% were 45 years of age or younger. No favourable risk profile, coronary angiographic features or cardiovascular outcome were observed in young compared with older patients.